KERAGAMAN DAN KELIMPAHAN MAMALIA DI PERKEBUNAN SAWIT PT SUKSES TANI NUSASUBUR KALIMANTAN TIMUR - Agus Priyono Kartono (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Conversion of primary forests into oil palm plantations in Indonesia is one of the major causes of habitat loss and threats to mammal diversity. Mammals are typically the taxa that receives negative impact of the convertions. This study provided information about the vegetation structure as habitat for mammals, as well as the diversity and abundance of mammals in high conservation value areas. Data collected through direct observation on the transect for large mammals and live-trapping for small mammals. Total species of mammals were found in all habitats types observed (karst habitats, palm oil plantation and secondary forests) are 25 species. In karst habitat was found as many as 17 species with a total abundance 12.41 individuals/ha, in the palm oil plantation area 12 species with a total abundance 4.29 individuals/ha, and in the secondary forest habitat as much as 6 species with a total abundance of 3.92 individuals/ha. Species diversity index in karst habitat H'=2.38±0.35, palm oil plantation area H'=2.13±0.67, and secondary forests H’=1.65±0.48. Hylobates muelleri, Rusa unicolor and Tragulus napu are a protected species found in karst habitat. Keywords: diversity index, high conservation value area, mammals, palm oil plantation